Feasibility of FitSkills for an Adult With Cerebral Palsy Using a Wheelchair in a Regional Setting: A Mixed Methods Case Study (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This study aims to assess the feasibility of FitSkills, a student-mentored community gym-based exercise intervention for an adult with cerebral palsy (CP) who uses a wheelchair in regional Australia. FitSkills was adapted to enable the participant to remain seated during the exercises, ensuring safety and convenience while undertaking the programme.Materials and Methods: This single-case mixed methods study used a convergent parallel design to evaluate feasibility across four domains: 1. acceptability, 2. practicality, 3. adaptation, and 4. limited efficacy. One adult participant (GMFCS IV) and a student mentor completed a 12-week gym-based intervention in a community gym in a regional city. Quantitative outcomes included attendance, safety, participation goals, strength, cardiovascular fitness, and quality of life. Qualitative data from interviews explored perspectives with categories distilled using qualitative description and deductive analysis into categories aligned with feasibility domains.Results: FitSkills was safe and acceptable, with 85% session attendance and only minor adverse events reported from the adult with CP (muscle soreness). Modest gains in strength and cardiovascular fitness were observed. Quality of life improved in two domains, anxiety and depression. Participation goals relating to work, established using Goal Attainment Scaling, were achieved, including increased attendance and greater involvement at work, such as more significant contributions to the operations of a photoshoot. Adaptations allowed full participation without requiring the participant to transfer from the wheelchair. The participant and student mentor described the mentor–participant relationship as a key enabler of motivation and sustained engagement.Conclusion: FitSkills has the potential to be feasible for adults with CP using wheelchairs when implemented in regional community gyms. Key adaptations include environmental and social modifications such as a student mentor and exercise strategies and show promise tailored for wheelchair use. Future studies should evaluate the feasibility of these strategies across diverse presentations in different regional community gym settings.Implications for Practice: Tailoring student-mentored support interventions to local contexts and emphasising social partnerships could promote physical activity participation and health for adults with CP in small regional cities. Future research is needed to evaluate FitSkills in regional settings, ensuring their adaptability to a broader range of disabilities and diverse presentations.